China's quest for "soft power" - Zhao, Yuezhi (Javnost (Ljubljana), 2013)
From establishing Confucius Institutes all over the world to mounting an advertising blitz in New York's Times Square, the Chinese state's multifacet edendeavour to strengthen its "soft power" has been highly visible and the subject of much recent political, journalistic, and scholarly attention. This paper locates the Chinese state's "soft power" quest within historical and geopolitical contexts and explores the profound contradictions in its underpinning political economy and cultural politics. While this campaign's state, industry, professional and moral imperatives appear self-evident and there are converging elite and popular interests in the project, its structural impediments seem to be insurmountable. Furthermore, there are irreconcilable tensions between a drive to pursue an elitist, technocratic, and cultural essentialist approach to global communication and acapacity to articulate and communicate an alternative global political and social vision that appeals to the vast majority of the world population in a deeply divided and crises-laden domestic and global order.
Keywords: Kitajska; mednarodni odnosi; komuniciranje; communication; politične komunikacije